2017
DOI: 10.1002/lio2.119
|View full text |Cite
|
Sign up to set email alerts
|

Expeditious emergency room referral pathway improves patient access to otolaryngology care

Abstract: ObjectivesHistorically at a multi‐hospital residency program, there was an unexpected number of non‐urgent consults from the county hospital emergency room (ER) that caused residents to make more trips between hospitals and come closer to violating duty hours. Moreover, there was also a poor follow‐up rate for these patients. An alternate pathway to redirect such consults to the Otorhinolaryngology–Head and Neck Surgery (ORL–HNS) clinic, staffed by an attending physician, was devised. This study illustrates ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Among six studies of facilitated appointment scheduling, five studies tested direct scheduling interventions to promote appointment attendance 9‐13 and one study compared attendance rates under three scheduling models: first available appointments, appointments within 2‐ and 4‐week windows 14 . Chan et al implemented an internet‐based referral system that enabled emergency department (ED) physicians to directly schedule patient follow‐up appointments with local community clinics and provide patients with printed appointment information and directions as part of their ED discharge paperwork, compared with usual care that required patients to schedule their own follow‐up appointments post‐discharge 9 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among six studies of facilitated appointment scheduling, five studies tested direct scheduling interventions to promote appointment attendance 9‐13 and one study compared attendance rates under three scheduling models: first available appointments, appointments within 2‐ and 4‐week windows 14 . Chan et al implemented an internet‐based referral system that enabled emergency department (ED) physicians to directly schedule patient follow‐up appointments with local community clinics and provide patients with printed appointment information and directions as part of their ED discharge paperwork, compared with usual care that required patients to schedule their own follow‐up appointments post‐discharge 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Messina et al facilitated patient phone calls to specialty providers from the ED in order to schedule follow‐up appointments prior to discharge 10 . Johnson et al tested a referral pathway that allowed ED nurses to schedule specialty follow‐up appointments for patients without requiring physician approval, and the specialty clinic expanded the number of follow‐up appointments available 11 . In Van Zyl et al, patients identified at a health fair as being at risk for glaucoma were offered pre‐scheduled appointments at community health centres, instead of being asked to call the health centre to schedule a follow‐up appointment 12…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Front-end processes are defined as the patient care processes that occur from the time of a patient’s initial arrival to a GES to the time a health care provider formally assumes responsibility, notably including the triage process[ 26 ]. Previous studies have demonstrated the efficacy of front-end operation targeted care pathways to improve the care of otolaryngologic and head and neck emergency patients[ 27 ], emergency presentations for cystitis[ 28 ], and common gynecologic emergencies[ 29 ]. In all studies, the identification of appropriate patients at triage for specifically designed care pathways resulted in a reduction in wait times and burden on health care providers without compromising safety.…”
Section: Discussionmentioning
confidence: 99%
“…The synergy of both LH and SS methodologies, that is LSS, seems to be one of the most innovative and effective approaches in "Operational Excellence" [25], and are effective quality improvement methods widely adopted by manufacturing industries that are currently also implemented in many health care settings [26]. In the field of health care, LSS has been used to address numerous health care problems [27], some of them include areas as: Trauma center [28], Cardiology [29], Surgery [30], operating room [31], Intensive care unit [32], rehabilitation ward [23], and Otolaryngology care [33].…”
Section: Introductionmentioning
confidence: 99%